PMO-079 Feasibility of bedside nasojejunal tube placement "blindly" or using an electromagnetic device. (28th May 2012) - Smith, K H; Smith, T; Leach, Z; Harding, S; Stroud, M
Abstract : Introduction: Some enterally fed patients require placement of a nasojejunal tube (NJT) which is often considered to need time-consuming, costly radiological or endoscopic input which can delay feeding commencement. This study examined the feasibility and accuracy of bedside NJT placement. Methods: As part of a study comparing nasogastric tube (NGT) with NJT feeding in dysphagic stroke, we assessed bedside NJT placement using a "blind" technique (standard 140 cm 8Fr tube) or an electromagnetic tracking device (Cortrak® with compatible Corflo® 8Fr tubes, donated by MerckSerono) to identify tube shape and hence likely position in the GI tract. In the parent study, 19 patients were randomised to receive an NJT and for the first 10, placement was blind while for the last nine the Cortrak® was used. The basic technique used to pass tubes was the same in both groups; tube measurement against patient's xiphisternum to ear to nose to anticipate length needed for tip to be in the stomach; passage of the tube a into the stomach; then advanced using gentle clockwise torque (a "flick" may be felt when the tube traverses the pylorus). Additional manoeuvres such as repositioning the patient, flushing small amounts of air/water, waiting 10 min before tube advancement and prokinetic administration were used as necessary. Correct placement in all cases was confirmed using aspirate from the stomach (acid pH), 1 aspirate from the small bowel (neutral/alkaline pH if obtained) and abdominal x-ray (AXR). Tubes placed using Cortrak® showed the expected pattern of small bowel placement on the tracking screen. Results: Bedside NJT placement was successful in 17 (89.5%) of the 19 patients—9/10 (90%) of blindly placed tubes and 8/9 (89%) Cortrak® placed tubes. All 17 NJTs were confirmed as correctly positioned on abdominal x-ray. Conclusion: NJTs can be safely placed at the bedside by trained staff in stroke patients to reduce endoscopy and radiology costs and achieve faster commencement of feeding. Placement can be achieved using a blind technique but use of an electromagnetic device can probably obviate the need for an AXR to check position. 2–4 Competing interests: K Smith grant/research support from: MerckSerono, T Smith: None declared, Z Leach: None declared, S Harding: None declared, M Stroud grant/research support from: MerckSerono. References: 1. National Patient Safety Agency . Reducing The Harm Caused By Misplaced Nasogastric Feeding Tubes In Adults, Children And Infants . NPSA Alert, 2011. Ref 1253. 2. Ackerman MH, Mick DJ, Bianchi C, et al. The effectiveness of the cortrak device in avoiding lung placement of small bore enteral feeding tubes. Am J Crit Care 2004;13 . 3. Phang J, Marsh W, Prager R. Feeding tube placement with the aid of a new electromagnetic transmitter. JPEN 2006;30 :S48–9. 4. Rao M, Kallam R, Flindall I, et al. Use of cortrak—an electromagnetic sensing device in placement of enteral feeding tubes. Proc Nutr Soc 2008;67 :E109.